2011
DOI: 10.1021/ef201141z
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Extruded Particles from Calcium Hydroxide and Cement for CO2 Capture

Abstract: The reversible reaction of CaO with CO2 can be used for CO2 capture. However, two challenging problems, i.e., loss-in-capacity and high attrition rate for CaO-based sorbents, must be solved before it can be practically applied. In this paper, sorbents with various CaO contents were prepared from calcium hydroxide and cement using a screw extruder and the physical and chemical properties of the sorbents were obtained. The mechanical properties of sorbent particles were tested by friability and compression teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 31 publications
3
91
0
Order By: Relevance
“…Consequently, the uniform distribution of mayenite among CaO micrograins leads to retarded sintering of calcium based sorbent. It has been reported that calcium based sorbents having mayenite as the binder exhibit stable and high CO 2 absorption capacities [12,13]. The final sorbents had a diameter of w1.5 mm with various lengths.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the uniform distribution of mayenite among CaO micrograins leads to retarded sintering of calcium based sorbent. It has been reported that calcium based sorbents having mayenite as the binder exhibit stable and high CO 2 absorption capacities [12,13]. The final sorbents had a diameter of w1.5 mm with various lengths.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the crushing strength of SGCS-made Ca 8 Zr 2 was 1.63 N, above the crushing criterion of 1 N suggested for the potential materials needed in the realistic fluidized bed system [50] and the abrasion index was lower than 8% (by mass) loss with the initial 10 min duration at the rotation 3000 r·min -1 , comparative to the sorbent prepared with Ca(OH) 2 and cement as sorbent precursors by Qin et al [44]. Therefore, Ca 8 Zr 2 would be applicable to CO 2 capture in the realistic fluidized bed system.…”
Section: Carbonation Conversion Of the Sgcs-made Cao/cazro 3 Sorbentmentioning
confidence: 69%
“…Finally, resistance to fragmentation and abrasion are very important criteria for sorbents applied in the realistic CO 2 capture system [43][44][45]. And the two criteria for the SGCS-made CaO/CaZrO 3 sorbent were further measured using a SHIMPO FGJ-5 crushing strength apparatus [NIDEC-SHIMPO (ZheJiang) Corporation, China] and an ordered abrasion tester (Dalian Smart tester Factory, China), respectively.…”
Section: Characterization Of the Synthesized Cao/cazro 3 Sorbentmentioning
confidence: 99%
“…The results demonstrated that Ca 30 /Al/Ti 3.4 has the best combination of stability and high capacity among the tested sorbents. Other studies have illustrated that if sintering can be effectively controlled, the sorption/desorption cycles should continue indefinitely [34,35]. According to the TG analysis, the synthetic sorbents yielded superior recovery performances (96-98%), proving that Ca/Al/Ti composed of LDHs is more stable than CaO-based sorbents.…”
Section: Co 2 Sorption Test By Tg Analysismentioning
confidence: 99%
“…The sorbent stability can be significantly enhanced by incorporating suitable inert particles into CaO, yielding well-distributed oxides within the calcium oxides. Impregnating CaO with an inert particle helps to avoid the deterioration of the spent sorbent, for example, of CaO/ SiO 2 [10], Ca/Al-oxide [11], Zr/Ca complex [12], limestone/kaolin [13], CaO/aluminate cement [14], and extruded particles of Ca(OH) 2 /cement [15].…”
Section: Introductionmentioning
confidence: 99%